2002
DOI: 10.1021/bi0121656
|View full text |Cite
|
Sign up to set email alerts
|

Connexin Family Members Target to Lipid Raft Domains and Interact with Caveolin-1

Abstract: Lipid rafts are cholesterol-sphingolipid-rich microdomains that function as platforms for membrane trafficking and signal transduction. Caveolae are specialized lipid raft domains that contain the structural proteins known as the caveolins. Connexins are a family of transmembrane proteins that self-associate to form cell-cell connections known as gap junctions and that are linked to cytosolic proteins, forming a protein complex or Nexus. To determine the extent to which these intracellular compartments interse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
196
2
5

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(221 citation statements)
references
References 81 publications
(107 reference statements)
15
196
2
5
Order By: Relevance
“…This lack of total PKC␥ activation is most likely due to the fact that cells have a rapid and robust PKC␥ turn-off mechanism including, among other things, dephosphorylation of PKC␥ by phosphatase (41). In brain tissues PKC␥ appears to prevent brain ischemia and is suggested as a target for ischemic preconditioning (40,(42)(43)(44). However, the role of PKC␥ in ischemic preconditioning was not clearly understood until recently (1, 2), when we demonstrated that PKC␥ is involved in gap junction control.…”
Section: Discussionmentioning
confidence: 99%
“…This lack of total PKC␥ activation is most likely due to the fact that cells have a rapid and robust PKC␥ turn-off mechanism including, among other things, dephosphorylation of PKC␥ by phosphatase (41). In brain tissues PKC␥ appears to prevent brain ischemia and is suggested as a target for ischemic preconditioning (40,(42)(43)(44). However, the role of PKC␥ in ischemic preconditioning was not clearly understood until recently (1, 2), when we demonstrated that PKC␥ is involved in gap junction control.…”
Section: Discussionmentioning
confidence: 99%
“…Transfection with connexin cDNAs can induce expression of other genes (32), and Cx43 has binding partners that associate with it (e.g., ZO-1 and caveolin-1) (33,34). Thus, we were concerned that expression of Cx43 could induce surface expression of other channels that were responsible for the currents that we were identifying as hemichannel-mediated.…”
Section: Cx43 With Egfp On the N Terminus (Egfp-cx43) Is Transported mentioning
confidence: 99%
“…The evidence for open hemichannels can be briefly summarized (and criticized [16][17][18][19].) The permeability and/or currents are inhibited by gap-junction blockers [10][11][12][13][14] (although most of the blockers are of dubious specificity).…”
Section: So Are These Really Hemichannel Currents?mentioning
confidence: 99%
“…Conversely, cells from connexin knockout animals do not show these properties, even though wild-type cells do [12,14]. (However, connexin transfection can induce changes in the expression of many other genes [15], and connexins have binding partners and might transport other channel molecules to the cell surface [16][17][18][19].) The permeability and/or currents are inhibited by gap-junction blockers [10][11][12][13][14] (although most of the blockers are of dubious specificity).…”
Section: So Are These Really Hemichannel Currents?mentioning
confidence: 99%